SOCIO-ETNO-PSYCHOLOGICAL CHARACTERISTICS OF SPIRITUAL PREPARATION OF YOUTH FOR MARRIAGE - Arapbaeva Damegul Kurbanovna (Zeta Repository, 2023)
The article discusses the influence of the psychological preparation of the bride and groom for marriage on the process of adaptation to family life. The study used a test of mental readiness for marriage [6]. This test consists of 16 questions and allows you to assess the level of moral readiness of young people for marriage according to a 5-point system.An empirical study was conducted among Kazakh families in the Konimekh district of the Navoi region and Uzbek families living in the Navbakhor district. In total, 200 respondents (100 brides, 100 grooms) took part in the study.